FENOMENA #KABURAJADULU: ANALISIS DAMPAK BRAIN DRAIN TERHADAP PEREKONOMIAN INDONESIA - Erlisya, Vyona; Aisyah Aulia; Ferika Clodya; Wahjoe Pangestoeti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The #KaburAjaDulu phenomenon that has gone viral on social media reflects the brain drain trend in Indonesia, where skilled labor and the younger generation choose to leave the country to seek better opportunities abroad. This hashtag symbolizes people's dissatisfaction with the economic, political and social conditions that are considered less supportive of their career development and welfare. Factors such as the high cost of education, limited job opportunities, low wages, and a non-conducive work environment are the main drivers of the movement of skilled workers. This research aims to analyze the impact of the brain drain phenomenon represented by the hashtag #KaburAjaDulu on the Indonesian economy, especially in terms of the loss of superior human resources that have an impact on national productivity and innovation. The research method used is descriptive qualitative through literature studies, social media analysis, and government policy studies. The results show that brain drain has the potential to hamper economic growth and reduce Indonesia's competitiveness at the global level. Therefore, skilled labor retention policies and strengthening the work environment are needed so that human resources can develop optimally in the country.